2015
DOI: 10.18553/jmcp.2015.21.12.1124
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Controller Medication Adherence, Risk of Exacerbation, and Use of Rescue Agents Among Texas Medicaid Patients with Persistent Asthma

Abstract: Adherence to long-term controller medications was suboptimal among patients with asthma. Adherent patients had fewer OCS claims, indicating that adherence to controller therapy is critical in preventing asthma exacerbations requiring OCS use. Although there was a positive relationship between adherence to long-term controller medication and SABA use, increased SABA use served as a predictor of increased OCS use, which indicates poor asthma control. Health care providers should be aware of OCS and SABA use amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 57 publications
3
46
0
Order By: Relevance
“…In the present study, notwithstanding the high rate of antiasthma therapy adherence, patients with a partial/poor adherence had a higher exacerbations risk (OR 2.54), in line with a recent review showing that a good adherence was associated with lower risk of severe asthma exacerbations . Indeed, adherence to antiasthma controller medications is one of the key drivers to improve persistent asthma management …”
Section: Discussionsupporting
confidence: 89%
“…In the present study, notwithstanding the high rate of antiasthma therapy adherence, patients with a partial/poor adherence had a higher exacerbations risk (OR 2.54), in line with a recent review showing that a good adherence was associated with lower risk of severe asthma exacerbations . Indeed, adherence to antiasthma controller medications is one of the key drivers to improve persistent asthma management …”
Section: Discussionsupporting
confidence: 89%
“…Poor adherence to asthma control medication is associated with the risk of developing AEs that require oral corticosteroids. 28 One of the relevant factors in medication adherence is incorrect inhaler technique in asthma treatment. 29 In contrast, patients suffering from more frequent exacerbations are likely to comply with their asthma medication regime.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of children and adolescents in the Texas Medicaid population revealed that average adherence to all types of controller strategies was only 32%. 17 In that study, only 4% of patients achieved an adherence rate of 80% based on the proportion of days covered. Clinicians, particularly in the context of a busy day of seeing patients, rarely have time or systems in place to reliably check a patient's inhaled controller refill history.…”
Section: Inhaled Asthma Controllersmentioning
confidence: 81%